2011
DOI: 10.1038/ejcn.2011.135
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition transition in the United Arab Emirates

Abstract: Objectives The UAE has undergone remarkable economic and social transformations over the past few decades. We present findings on the prevalence of overweight and obesity, dietary and activity patterns among Emiratis in 2009/10, and explore associated urbanization and wealth factors. Methods A cross-sectional study was conducted in 628 randomly-selected households in all seven emirates. Sociodemographics, 24-hour dietary recalls, physical activity and anthropometric data were collected from adult females (≥1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
199
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(208 citation statements)
references
References 44 publications
7
199
2
Order By: Relevance
“…The results highlight a high prevalence and increasing trend of adult obesity in many countries (44,(87)(88)(89)(90). The regional average of adult obesity (24%) exceeds the worldwide average (9.8% in men and 13.8% in women) (142), as well as estimates reported from South Asia (1.2-2.9%), but it is lower than the average prevalence of adult obesity in North America (29.2%) (142).…”
Section: Discussionmentioning
confidence: 66%
“…The results highlight a high prevalence and increasing trend of adult obesity in many countries (44,(87)(88)(89)(90). The regional average of adult obesity (24%) exceeds the worldwide average (9.8% in men and 13.8% in women) (142), as well as estimates reported from South Asia (1.2-2.9%), but it is lower than the average prevalence of adult obesity in North America (29.2%) (142).…”
Section: Discussionmentioning
confidence: 66%
“…According to a large-scale study in the UAE, almost 28% of male adolescents and 40% of female adolescents were overweight or obese. Furthermore, physical activity levels were low, especially among female Emiratis and those living in urban areas (30).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, adolescence appears to be an ideal time to influence choices and shifts in behaviour and attitudes. Eating behaviours and food choices are usually acquired in childhood but these are further shaped during adolescence and are influenced by a range of factors such as the media, socioeconomic status, peers, family and personal nutritional knowledge (19,28,30).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study done in the United Arab Emirates revealed that consumption of caloric beverages like fruit juices and sugared sodas accounted for up to 70% of liquid intake [6]. A study among university students at Ajman revealed that majority of students preferred energy drinks over nutritional health drinks [7].…”
Section: Introductionmentioning
confidence: 99%